The Future of You - Amanda Cheng (Opticon1826, 2008)
The actress Billie Burke once said, “Age is of no importance, unless you are cheese”. How true is this in the U.K, and what does this mean for the elderly of the future? This article highlights current issues on employment and isolation, explores current standards of care, and considers an ever-increasing trend towards inadequately met health and social needs for the future generation of geriatrics. It will also look at recent policies introduced to acknowledge such problems, and strategies aimed at improving matters for the elderly population
Keywords: geritatrics; social care; isolation; employment